SURDOWAY.UZ EDUCATIONAL PLATFORM AS A DIGITAL TOOL FOR TEACHING LATIN-BASED FINGERPRINT AND SIGN LANGUAGE (Web of Teachers: Inderscience Research, 2025)
This article analyzes the Surdoway.uz educational platform, designed to teach people with hearing impairments the Latin-based fingerspelling alphabet and elements of sign language. The paper examines the platform's key features, including interactive learning modules, video materials, and a visually oriented interface that ensures accessibility for hard-of-hearing and deaf users. The study's findings demonstrate that Surdoway.uz promotes the development of communication skills, increases the accessibility of inclusive education, and integrates modern approaches to sign language teaching in a digital environment.